The Relationship Between Smartphone Addiction and the Interpersonal Competence of Chinese Private College Students: A Moderated Mediation Model - Su Y; Yan Z; Lin W; Liu X (Psychology Research and Behavior Management, 2024)
Yunjing Su,1,2 Zhonglian Yan,1 Wenqi Lin,1 Xuelin Liu1 1Faculty of Education, Northeast Normal University, Changchun, Jilin, People’s Republic of China; 2School of Child Welfare, Changchun Humanities and Sciences College, Changchun, Jilin, People’s Republic of ChinaCorrespondence: Yunjing Su, Faculty of Education, Northeast Normal University, No. 5268 Renmin Street, Changchun, Jilin Province, 130024, People’s Republic of China, Email suyj774@nenu.edu.cnPurpose: As an aspect of the lives of private college students in China, interpersonal competence (IC) is important to their socialization and employment competence. This study aimed to investigate the relationship between Chinese private college students’ smartphone addiction (SPA) and IC, the mediating effect of negative emotions (NE), and the moderating effect of psychological resilience (PR).Samples and Methods: Using simple random sampling, 5473 Chinese private college students (male 74.5%, urban household registration 51.6%, served as a student leader 31.5%) were recruited.Results: The results showed that (1) SPA positively predicted IC; (2) NE partially mediated the relationship between SPA and IC; and (3) PR moderated the relationships between SPA and NE, NE and IC, SPA and IC.Conclusion: These findings provide a new perspective to improve Chinese private college students’ socialization and their employment competitiveness.Keywords: Chinese private college students, interpersonal competence, negative emotions, psychological resilience, smartphone addiction